Effects of tarragon (Artemisia dracunculus) powder on broiler performance parameters and histopathology of internal organs - Tunç, Muhammet Ali; Yıldırım, Serkan; Yörük, Mehmet Akif (Austral Journal of Veterinary Sciences, 2019)
The aim of this study is to evaluate whether the addition of tarragon in the diet of broiler chickens affects their performance and histological structures of internal organs. A total of 240 day-old Ross 308 male broiler chickens were used. The experiment included four treatment groups, with six replications per treatment. The experiment lasted 42 days and the chickens were provided with feed and water ad libitum. Experimental groups were given basal diet only (control group), basal diet + 0.1% tarragon powder (T1 group), basal diet + 0.2% tarragon powder (T2 group) and basal diet+ 0.5% tarragon powder (T3 group). The tarragon additive did not affect the values of the daily feed intake (DFI) and feed conversion rate (FCR) during the trial periods, while the highest daily weight gain (DWG) was recorded in the control group (P<0.05) on days 29-35 and 36-42. The longest jejunum villi was observed in the T2 group (P<0.05). The results indicate that different amounts of tarragon powder additive did not affect the DFI and FCR as performance parameters, while they had a negative impact on DWG. In addition, the livers, kidneys and intestinal tissue structures did not change. Therefore, the tarragon powder had no negative effects on the health of chickens.